Sports facilities in urban areas: trends and development considerations - Barghchi, M.; Omar, D.; Aman, M.S. (Universiti Putra Malaysia Press, 2010)
Sports and sports facilities development have improved rapidly over the past years in Malaysia. However, such improvements are inadequate compared to the overall development of sports at international level. Through preliminary interview with the managers, it was learnt that the sports facilities are underutilised and people do not use them. In addition, an increase in the amount of public money being spent on the sports facilities, as well as the increase in the number of sports facilities, necessitates the demand to investigate issues surrounding sports facilities development. Universally, there is a current sports facilities development boom. Recent developments are providing new roles for sports facilities in urban areas. However, it is accompanied by changing the cities strategies for large scale development. Although there are many research findings, there are still on-going debates on how to effectively use public money for sports facilities development. Through reviewing the current literature, it can be concluded that the impacts of sports facilities and the ability to affect urban surrounding areas depend on a wide range of factors, including location, context, and usage of the facilities, as well as the culture of sports among people. The aim of this paper is through reviewing the current literature on sports facilities worldwide to identify the gap and address issues on the development of sports facilities in Malaysia. The paper argues that simultaneously with the current interest on sports and sports facilities development in Malaysia, there is a need for a new perspective and a new approach for sports facilities development in the future.